PEMANFAATAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI CATU DAYA LISTRIK PADA KELOMPOK USAHA PERTANIAN - I G N Janardana; I W Arta Wijaya (Program Studi Teknik Elektro UNUD, 2021)
It is time for solar power plants to supply electricity to agricultural businesses to avoiddependence on oil-fired electricity. Most agricultural businesses find it difficult to get electricitybecause they are located far from the center of the PLN network. The purpose of this study wasto determine the potential and design of PLTS for electricity needs in agricultural businesses.The method of analysis was carried out descriptively by calculating the primary data. The resultsof the analysis on each load requirement show that for a 500 watt load, 24 panels series SP-100-M36 Part Number 53-067, SR-500 - S-12V inverter, minimum battery 4666.66 Ah 47 unitsof Model SMT12100S are needed, 1000 watt load required 47 panels series SP-100-M36,Growatt 1000S inverter, 9333.33 Ah batteries 94 pieces Model SMT12100S, 1500 watt loadrequired 71 panels specification series SP-100-M36, Growatt inverter specification 1500Sminimum capacity battery 14000 Ah 140 pieces Model SMT12100S, 3000 watt load required142 pieces of SP-100-M36 specification panels, Sunny Boy 3000 TL inverter specifications,batteries with a minimum capacity of 28000 Ah 280 SMT12100S.Key words: Electric power, renewable energy, PLTS.